Analisis Kebutuhan Volume Pekerjaan Struktur Pelat Lantai Metode Konvensional - Alfianarrochmah, Ilma; Joko Herlambang, Rayfandy; Putri Deni, Delista; Kurnianingsih, Oktavia; Lautan Wijaya Nusantara, Johan (Faculty Of Engineering University 17 August 1945 Semarang, 2025)
Floor slabs are important structural elements in building construction that function as floor coverings and withstand various loads. The purpose of this study is to identify the implementation method of the slab work and analyze the material requirements for the slab work of the Joglo Elementary School Building Construction project. This research applies quantitative research type. The volume calculation method is manual (conventional). The calculation analysis is only limited to the work of reinforcing iron, formwork, and concrete. The implementation of floor slab work in this project includes reinforcement work, formwork work, casting work, formwork demolition work, and floor slab concrete maintenance work. The reinforcement requirement for the 1st floor needs 8,551.02 kg, the second floor 17,102.04 kg, and the third floor 17,102.04 kg. The formwork requirements for the 1st floor slab amounted to 1038.34 m2, the second floor amounted to 1038.24 m2, and the third floor amounted to 1038.34 m2. The casting requirement for the 1st floor slab is 103.83 m3, the 2nd floor is 124.60 m3, and the 3rd floor is 124.60 m3.